Structural system selection and design of Zhangzhou Opera House Fujian Province. Issue 1 (January 2021) - Yang, Songlin; Ren, Qingying; Liu, Wenting; Zhang, Xiaomeng
Abstract: Zhangzhou Opera House adopts the complex structure system of petal shape. According to the building shape and architectural layout, the structure combines the steel truss for large-span space and the frame-shear wall structure surrounding. This article introduced its structural system, multi-line defense line arrangement and anti-seismic performance objectives, and summarized the structural characteristics of the overall structure, especially focusing on key issues such as setting the ring floor beam to resist the extroversive forces, anti-seismic performance of key components and the design of the junction between the steel truss and concrete structure. The results show that the structure has strong adaptability to the building shape with suitable seismic performance, and fulfilling both the requirements of seismic performance design and the structural safety.